Conservation of Dhulikhel - Bhandari, Puspa; Karki, Rachana; G.C, Riya; Pandey, Ritika; Bhurtel, Sumnima; Acharya, Yojana; Manandhar Joshi, Shailita (KEC Journal of Science and Engineering, 2024)
This paper outlines a comprehensive conservation project addressing historical and natural heritage in Dhulikhel, an endangered settlement in Kavrepalanchowk. Undertaken in two phases, the initiative began with inventory and documentation conducted by the 2075 batch of architecture students of Kathmandu Engineering College. The final phase involved identifying existing issues by our team and proposing solutions to prevent further deterioration. The primary objective is the conservation of Dhulikhel, focusing on reviving the settlement by discouraging out-migration and creating diverse employment opportunities centered on its five main celebratory nodes (Chowk).